PERTUMBUHAN DAN PRODUKSI INDIGOFERA (Indigofera zollingeriana) PADA BERBAGAI DOSIS PUPUK BIO-SLURRY - I W. D., Jaya; Roni, N. G. K. (Jurnal Peternakan Tropika, 2016)
The study aimed to determine the growth and production of Indigofera zollingeriana at various dosages of bioslurry fertilizer was conducted for 10 weeks at Research Station Faculty of Animal Husbandry Udayana University at Pengotan Village, Bangli Districts, Bangli regency. The study used randomized block design (RBD) with four doses of offering bioslurry fertilizer as treatments: D0: without bioslurry fertilizer, D5: 5 ton/ha, D10: 10 ton/ha and D15: 15 ton/ha. The four treatments ware devided in four blocks as replicate, so there ware 16 plots as an experiment unit. Variables observed ware growth, production and characteristics. Result of the study showed that the offering of bioslurry fertilizer could increase the growth of Indigofera zollingeriana and tends to increase it production. Dose 5 tons/ha, 10 tons/ha, and 15 ton/ha increase the number of branches and number of leaves compared to control.  Dose bioslurry 5 ton/ha results leaf dry weight, stem dry weight, total dry weight of forage and leaf area tended (P>0.05) was higher than other treatments. Based on the results of the study it concluded that the bioslurry fertilizer could increase growth Indigofera zollingeriana. Dose 5 tons/ha, 10 tons/ha, and 15 ton/ha were increase the number of branches and number of leaves compared to control, and production of the most well Indigofera zollingeriana produced on the treatment of bio-slurry 5 ton/ha.
Keywords: , production, Indigofera zollingeriana, bio-slurry, fertilizers dose